(3TQM Ydi eHGQc GdabgGA hLQM eYGRd GdSagGAs - (3YHjOGddg fYeGf GdUdGMjs ((3CMeO Hf eMeO GdTgjQ HGHf GdXQja s)
(3ChdgG (B:s
(3SHMGf GdPiCfRd GdeJTGHgGJ hLYd GdGeJfGY Yf EJHGY JChjdgG CeQkG LejdkG s
(3BNQgG (B:s
(3Je GdcJGH GdeHGQc GdeSei HeHGQc GdabgGA s
(3hgj efXheI ai GdNdGajGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfajs